A term as a kind of jural facts-states - Volkova, I.; Волкова, І. (Visegrad journal on human rights. – 2019. – № 1 (Vol. 2). – P. 31-36, 2019)
Досліджено сутність строків як різновиду юридичних фактів-станів. Здійснено системний аналіз визначення місця строків у теорії юридичних фактів-станів. Висвітлено питання класифікації строків.

The article is devoted to problems of terms. The author pays attention to system analysis of terms as jural facts-states. Moreover the author represents kinds of terms.

Исследована сущность сроков как разновидности юридических фактов-состояний. Осуществлен системный анализ определения места сроков в теории юридических фактов-состояний. Освещены вопросы классификации сроков.
Строк як різновид юридичних фактів-станів
Volkova, I. A term as a kind of jural facts-states / Irina Volkova // Visegrad journal on human rights. – 2019. – № 1 (Vol. 2). – P. 31-36.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; юридичний факт; legal fact; юридический факт; юридичний факт-стан; legal fact-state; юридический факт-состояние; строк; term; срок; термін; класифікація строків; classification of terms; классификация сроков